5*(m+1)-3*(2m+1)=4*(5-m)

Simple and best practice solution for 5*(m+1)-3*(2m+1)=4*(5-m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5*(m+1)-3*(2m+1)=4*(5-m) equation:


Simplifying
5(m + 1) + -3(2m + 1) = 4(5 + -1m)

Reorder the terms:
5(1 + m) + -3(2m + 1) = 4(5 + -1m)
(1 * 5 + m * 5) + -3(2m + 1) = 4(5 + -1m)
(5 + 5m) + -3(2m + 1) = 4(5 + -1m)

Reorder the terms:
5 + 5m + -3(1 + 2m) = 4(5 + -1m)
5 + 5m + (1 * -3 + 2m * -3) = 4(5 + -1m)
5 + 5m + (-3 + -6m) = 4(5 + -1m)

Reorder the terms:
5 + -3 + 5m + -6m = 4(5 + -1m)

Combine like terms: 5 + -3 = 2
2 + 5m + -6m = 4(5 + -1m)

Combine like terms: 5m + -6m = -1m
2 + -1m = 4(5 + -1m)
2 + -1m = (5 * 4 + -1m * 4)
2 + -1m = (20 + -4m)

Solving
2 + -1m = 20 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
2 + -1m + 4m = 20 + -4m + 4m

Combine like terms: -1m + 4m = 3m
2 + 3m = 20 + -4m + 4m

Combine like terms: -4m + 4m = 0
2 + 3m = 20 + 0
2 + 3m = 20

Add '-2' to each side of the equation.
2 + -2 + 3m = 20 + -2

Combine like terms: 2 + -2 = 0
0 + 3m = 20 + -2
3m = 20 + -2

Combine like terms: 20 + -2 = 18
3m = 18

Divide each side by '3'.
m = 6

Simplifying
m = 6

See similar equations:

| 3m=7m-16 | | x+487-69=3865 | | p(x)=80-3x | | X+9=8x^2+16 | | -30u+(-6u)= | | 8x^2+16x= | | 2x+4x+40=180 | | 2(y-1)+4y=8 | | 15x+20(x-5)=285 | | 4x^2+9x-9= | | 9x^2-7x-116=0 | | 9y-3y-2y=28 | | -1=-3x-2 | | Y=-3(0)-2 | | 2z-6z+1=9 | | Y=-3(-1)-2 | | 2d+8=2 | | 5w+3w+2w=60 | | 5k+2(k+1)=24 | | -7m-m+1=9 | | 3z-z=10 | | 4x^2+5x=-3 | | 8-y=9 | | -3-y=-1 | | -2-y=-1 | | 6=-3(x-5) | | 63=5x^2-26x | | x-(-38)=43 | | 8n+18=360 | | 7y=39 | | 7w-15-5w=43 | | 4+x-9+x=7 |

Equations solver categories